Attitudes toward Women’s Roles, Marital Satisfaction, and Hwa-Byung among Korean Married Couples - Kim, Tae Hoon; Kim, Eunha; Nam, Hyeon Suk (International Journal for the Advancement of Counselling, 2019)
This study surveyed 150 middle-aged Korean wives and husbands and examined the hypothesized path model that gender-role attitudes – in this case, those of women – would be associated with marital satisfaction, which, in turn, would be related to Hwa-Byung. Hwa-Byung is a Korean culture-bound syndrome and means “anger illness.” The results of structural equation modeling using an actor-partner interdependence strategy indicated that husbands’ egalitarian attitudes toward women’s roles predicted their own and their wives’ marital satisfaction, and marital satisfaction was then associated with decreased Hwa-Byung symptoms. However, wives’ attitudes toward women’s roles was not related to their own or their husbands’ marital satisfaction. These results imply that what is crucial in understanding marital satisfaction and Hwa-Byung among Koreans is not wives’ attitudes toward women’s roles, but rather husbands’ egalitarian attitudes toward women’s roles. The implications of the present study for Hwa-Byung treatment and couple counseling were discussed.
Keywords: Actor effect; Attitudes toward Women’s roles; Hwa-Byung; Korean married couples; Marital satisfaction; Partner effect